Visualization of mass transfer in mixing processes in high solid anaerobic digestion using Laser Induced Fluorescence (LIF) technique. (15th May 2021) - Hu, Yuying; Zhang, Shihao; Wang, Xin; Peng, Xiaoming; Hu, Fengping; Wang, Chuqiao; Wu, Jing; Poncin, Souhila; Li, Huai Z.
Graphical abstract: Highlights: A novel approach for quantifying HSAD's mass transfer was proposed. In the mixing process, feedstock tended to accumulate around the 1st stage impeller. HSAD's mixing homogeneity remained unachieved after 4 h. Prolonging the mixing time could not significantly improve the mass transfer. The novel measuring approach visualized the mass transfer in HSAD. Abstract: High solid anaerobic digestion (HSAD) is a promising technology for the treatment of organic waste. Mixing process in HSAD is quite difficult with long mixing time, poor homogenization, significant short-circuiting and stagnant zones. However, the mass transfer in mixing process in HSAD has not been visualized due to the lack of a proper method. In this study, a novel approach for experimentally quantifying the mass transfer in HSAD's mixing process was proposed in a mixing tank equipped with multistage impellers by means of the Laser Induced Fluorescence (LIF) technique. Flow field was investigated for better illustrating the mass transfer, thus Particle Image Velocimetry (PIV) and Computational Fluid Dynamics (CFD) technique were conducted for flow field measurement. The obtained results revealed that the feedstock tended to accumulate around the impeller in the HSAD system, especially near the 1st stage. The tracer diffused rapidly around the 1st impeller in t = 10 s, but the diffusion around the 2nd impeller was quite tough even after 4 h 08 min 23 s. And prolonging mixing time could not significantly improve the flow pattern along with the mixing. In this study, new insight was thrown into the visualization of the mass transfer in mixing process within a HSAD reactor. The visualization of mass transfer in the mixing process in HSAD could offer reference information to the study of the mixing process of HSAD even in full-scale.